Malt friability and quality prediction in malting barley breeding (Hordeum vulgare L.) - Huerta Zurita Ramón; Zamora Díaz Mauro R.; Solano Hernández Salomón; López Cano Martha Laura (Revista Mexicana de Ciencias Agrícolas, 2018)
Malt friability is used to measure barley endosperm modification during malting. This parameter has been proposed as a useful tool for advanced material evaluation in malting barley breeding programs for its correlation with quality factors. The aim of this study was to evaluate the malt friability analysis in quality prediction during malting barley breeding and determine the minimum value for genotype selection. Samples evaluated in two crop irrigation cycles (winter 2008-2009 and winter 2009-2010) were the advanced lines (> F7) M171, M173, M174, M175, M10542 and varieties Adabella, Alina, Armida, Esmeralda and Esperanza; grown in Celaya, Guanajuato, Mexico. Malt friability was correlated with fine grind extract (r= 0.631), total protein (r= -0812 ), diastatic power (r= -0.506) and Kolbach index (r= 0.522), however, Esmeralda, Esperanza, M171 and M10542 showed no correlation to fine grind extract (FGE) and Kolbach index (KI). Wide variation in malt friability (30- 85%) was observed, mostly by protein changes, thus the minimum value for genotype selection in breeding could not be determined based on FGE, viscosity wort, KI and extract difference. Significant friability changes (> 20%) and FGE (> 0.98%) appeared with protein variation greater than 1.40%. Considering these results, malt friability is not a reliable tool in discriminating genotypes for malting barley breeding, where protein changes are common among filial generations and crop cycles.